Aspects in oat breeding: nutrition quality, nakedness and disease resistance, challenges and perspectives. (7th September 2017) - Gorash, A.; Armonienė, R.; Mitchell Fetch, J.; Liatukas, Ž.; Danytė, V.
Abstract: Traditionally, the oat crop ( Avena sativa ) has been neglected in a number of respects, cultivated in cropping areas not optimal for wheat, barley or maize. In recent years the interest in oats has increased, particularly because of its dietary benefits and therapeutic potential for human health. The uniqueness and advantages of naked oats over other popular cereals, due to its potentially valuable nutritional composition, have been well studied and reported, opening new market "niches" for oats. Despite the well‐documented benefits, the status of the oat crop is still fragile, due to many reasons. The area cultivated for the oat crop is much less compared with other cereals, and therefore commercial efforts in oat breeding are less. Oat groat yield is lower than other cereals such as wheat and the nutritious uniqueness has not been reflected in agreeable market prices. The same price still exists for both naked and conventional/covered oats in the world grain market. The absence of visible market competitiveness, and some of the oat biological drawbacks, including low grain yield, keeps the oat crop as a lower profitability minor crop. This review is intended to analyse and summarise main achievements and challenges in oat genetics, agronomy and phytopathology to find possible ways of oat improvement and future perspectives for oat breeding. Abstract : Traditionally, oat has been neglected, considered non‐profitable. In recent years interest in oat has increased, but in spite of well‐documented benefits, the status of oat is still fragile. This review analyses the challenges and recent achievements in oat genetics, agronomy and phytopathology to find possible ways of oat improvement and future perspectives for oat breeding.